Severe neonatal legionellosis associated with use of home humidifiers – A case report. (October 2020) - Mitting, Rebecca; Rajagopal, Veena; Grossman, Thalita; Whittaker, Elizabeth; Chalker, Victoria; Lai, Sandra; Hoffman, Peter; Atkin, Sara; Qureshi, Sabeena; Hatcher, James
Highlights: Neonatal Legionella pneumophila infection is rare and mortality is high. There has been limited success with the use of extracorporeal membrane oxygenation, with reported mortality in infants of 88%. In view of the rapid growth of the worldwide humidifier market, the association between neonatal legionella and use of cold mist humidification may be important. Consideration of legionellosis should be given for any neonate presenting with severe sepsis or respiratory compromise who has been exposed to aerosol generating home humidifiers. In spite of previously reported high mortality in infants, we report a case of a 5 day old infant that demonstrates that excellent outcome is possible with early escalation to VA ECMO. Abstract: Neonatal Legionella pneumophila infection is rare and mortality is high. There has been limited success with the use of extracorporeal membrane oxygenation, with reported mortality in infants of 88%. We present the case of a 5 day old infant with neonatal legionellosis who had been exposed to cold mist humidifiers in the home, filled from a domestic water supply contaminated with legionella. The infant was treated with veno-arterial extracorporeal membrane oxygenation and survived with subsequently normal neurodevelopmental follow-up. In view of the rapid growth of the worldwide humidifier market, the association between neonatal legionella and use of cold mist humidification may be important. Consideration of legionellosis should be given for any neonate presenting with severe sepsis or respiratory compromise who has been exposed to aerosol generating home humidifiers. In spite of previously reported high mortality in infants, this case demonstrates that excellent outcome is possible with early escalation to VA ECMO.